# Is there a quicker way to solve this integral: $\int \frac{3-\cos(x)}{(1+2\cos(x))\sin^2(x)}dx$?

The integral is: $$\int \frac{3-\cos(x)}{(1+2\cos(x))\sin^2(x)}dx$$ This is the way I approached it: $$\tan\left(\frac{x}{2}\right)=u\\dx=\frac{2}{\sec^2\left(\frac{x}{2}\right)}du$$ By using trigonometric identities we get: $$\sin(x)=\frac{2u}{1+u^2};\ \cos(x)=\frac{1-u^2}{1+u^2};\ \sec^2\left(\frac{x}{2}\right)=1+u^2$$ Therefore the integral now becomes: $$2\int \frac{3-\frac{1-u^2}{1+u^2}}{\left(1+2\left(\frac{1-u^2}{1+u^2}\right)\right)\left(\frac{2u}{1+u^2}\right)^2(1+u^2)}du=$$ $$\int\frac{(1+2u^2)(1+u^2)}{u^2(3-u^2)}du$$ By dividing the two polynomials we get: $$\int\left(-2-\frac{9u^2+1}{u^2(3-u^2)}\right)du$$ Using partial fractions we get to the simplified form: $$\int\left(-2-\frac{1}{3u^2}+\frac{28}{3(3-u^2)}\right)du$$ $$-2u-\frac{1}{3u}+\frac{28\sqrt3}{9}\int\frac{1}{1-\left(\frac{u}{\sqrt3}\right)^2}du \\ -2u-\frac{1}{3u}+\frac{28\sqrt3\tanh^{-1}{\left(\frac{u}{\sqrt3}\right)}}{9}+C$$ By substituting back in for $u$, we get the solution: $$\bbox[5px,border:2px solid black]{\frac{28\sqrt3\tanh^{-1}{\left(\frac{\tan\left(\frac{x}{2}\right)}{\sqrt3}\right)}}{9}-2\tan\left(\frac{x}{2}\right)-\frac{1}{3}\cot\left(\frac{x}{2}\right)+C}$$ My question is, as you can understand from the title, is there any easier and faster way to solve this integral? If so, how? Thank you.

• Considering the final result, it's likely that this is already as simple as it can be. – DanielWainfleet Feb 3 '17 at 3:17

## 2 Answers

HINT

One can look for coefficients of identity $$f(y)=\frac{3-y}{(1+2y)(1-y^2)}=\frac A{1+2y}+\frac B{1-y}+\frac C{1+y}:$$ $$A=\lim_{y\to -\dfrac12}(1+2y)f(y) =\frac{14}3,$$ $$B=\lim_{y\to 1}(1-y)f(y) = \frac13,$$ $$C=\lim_{y\to-1}(1+y)f(y) = -2$$ and then find the integrals through the universal trigonometric substitution and known integrals $$\int\dfrac{\mathrm dx}{1-\cos(x)}=\dfrac12\int\dfrac{\mathrm dx}{\sin\left(\dfrac x2\right)} = -\cot\left(\dfrac x2\right)+constant,$$ $$\int\dfrac{\mathrm dx}{1+\cos(x)}=\dfrac12\int\dfrac{\mathrm dx}{\cos\left(\dfrac x2\right)} = \tan\left(\dfrac x2\right)+constant.$$

• Perfect! Thank you very much. – user372003 Feb 3 '17 at 3:29
• You are welcome) – Yuri Negometyanov Feb 3 '17 at 3:31
• Ah, the good old partial fractions decomposition in disguise +1 – imranfat Feb 3 '17 at 4:27

You can simplify the calculation by using a trigonometric identity and partial fractions before doing the Weierstrass substitution: since $\sin^2{x}=1-\cos^2{x}$, the initial fraction simplifies to $$\frac{3-\cos{x}}{(1+2\cos{x})(1+\cos{x})(1-\cos{x})} = \frac{14/3}{1+2\cos{x}} + \frac{-2}{1+\cos{x}} + \frac{-1/3}{1-\cos{x}}.$$ The middle fraction simplifies to a multiple of $\frac{1}{2}\sec^2{\left(\frac{1}{2}x\right)}$, which easily integrates to $-\tan{\frac{1}{2}x}$, and similarly the last fraction is a multiple of $\frac{1}{2}\csc^2{\left(\frac{1}{2}x\right)}$, which integrates to $-\cot{\frac{1}{2}x}$; the other fraction really does need the Weierstrass substitution, but at least the algebra is now much simpler!

• How did you get rid of the 3 on the numerator? – user372003 Feb 3 '17 at 3:41
• Good point. I've fixed the calculation. – Chappers Feb 5 '17 at 2:36